Honey bee – Passiflora edulis Sims. (Passifloraceae) pollination found in the Pachamalai Hills, Eastern Ghats of Tamil Nadu - V, Nandagopalan; V, Anburaja; M, Johnson Gritto; R, Uma Maheswari (Journal of Research in Biology, 2012)
Pollination is the process of fertilization in higher plants. In flowers, pollen is delivered to the stigma through a wide range of mechanisms that insure an appropriate balance in the genetic makeup of the species. For many plants, flowers are vital organs of reproduction containing both male and female gametes. For bees and other nectar-feeding animals, flowers are a source of food. In Passiflora edulis, pollen is distributed by bees. The flower is the device by which the plant recruits the bee. The bees and P. edulis have evolved an interdependent relationship